2013
DOI: 10.11646/zootaxa.3626.4.1
|View full text |Cite
|
Sign up to set email alerts
|

External morphology and osteology of Darevskia rudis (Bedriaga, 1886), with a taxonomic revision of the Pontic and Small-Caucasus populations (Squamata: Lacertidae)

Abstract: A broad sample of Darevskia rudis from the main part of its range was reviewed with regard to external morphology (dis-criminant, UPGMA, MST and ANOVA analyses) and osteology. Darevskia bithynica is raised to species rank, with two subspecies: D. b. bithynica and D. b. tristis. The other subspecies are fairly similar (D. r. rudis being the most different). Two singular populations are described as subspecies: D. r. mirabilis ssp. nov. from Kaçkar Mountains, geographically adjoins the otherwise different D. r. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…This sample was taken from 23 lizard populations and collected across the range of species in North Anatolia in spring (table 1). In a previous study by Arribas et al (2013), specimens from northern Anatolia and the Middle Taurus Mountains in Anatolia were examined for external morphology and osteology, and Darevskia bithynica was raised to species rank, with two subspecies: D. b. bithynica and D. b. tristis in the western and Black Sea Region of Anatolia. Following this taxonomic arrangement, some populations, such as those from Kirazlı Plateau-Uludag to Kapısuyu-Kurucaşile (see table 1), examined for parasites would be ascribed Table 1.…”
Section: Collection and Examination Of Lizardsmentioning
confidence: 99%
“…This sample was taken from 23 lizard populations and collected across the range of species in North Anatolia in spring (table 1). In a previous study by Arribas et al (2013), specimens from northern Anatolia and the Middle Taurus Mountains in Anatolia were examined for external morphology and osteology, and Darevskia bithynica was raised to species rank, with two subspecies: D. b. bithynica and D. b. tristis in the western and Black Sea Region of Anatolia. Following this taxonomic arrangement, some populations, such as those from Kirazlı Plateau-Uludag to Kapısuyu-Kurucaşile (see table 1), examined for parasites would be ascribed Table 1.…”
Section: Collection and Examination Of Lizardsmentioning
confidence: 99%
“…Darevskia rudis obscura adults are usually smaller than those of D. r. rudis from habitats with similar environmental conditions and reach higher elevations. Darevskia valentini has brighter dorsal coloration and smoother scales than most of the D. rudis populations, although some populations geographically intermediate between D. valentini and D. r. obscura (which Darevsky referred to as D. r. macromaculata) have individuals that are difficult to attribute to either nominal species [Arribas et al (2013) even synonymized D. r. macromaculata with D. r. obscura]. Some specimens of the nominal species of the 'rudis' clade show individual traits that are more similar to those of other species of the clade than to those of the species to which they belong.…”
Section: Discussionmentioning
confidence: 98%
“…valentini and D. r. rudis (Tarkhnishvili et al, 2013). Arribas et al (2013) suggested a conspecific status for all forms within D. rudis and synonymized D. r. macromaculata with D. r. obscura.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Darevskia [3] which have some taxonomic revisions, have been investigated in numerous studies. Most of the subspecies were evaluated to species rank because of the detailed morphological and molecular studies [3,6,15,17,26]. Although osteological data have an important role to address its taxonomic position and attain a better understanding of the evolution of lizards, the literature on skeletal osteology of lizard is quite limited.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, numerous molecular studies have been conducted for the species examined [18,19,26,27]. Although there are many studies conducted on their taxonomy, genetics and morphology, detailed and comprehensive osteological studies of the lizard families including Lacertidae received relatively limited attention [5,6,22,28]. In this study, we aim to provide detailed comparative osteological descriptions of D. parvula and D. adjarica, and to shed some more light on the osteology and phylogeny of these lacertids.…”
Section: Introductionmentioning
confidence: 99%